Periodicity in Steller’s eider (Polysticta stelleri) population size and density on the Arctic Coastal Plain, Alaska, revealed using generalized additive models - Erik E. Osnas (PLoS ONE, 2026)
Annual population and spatial density estimates are needed for the threatened Alaska-breeding population of Steller’s eiders ( Polysticta stelleri ) to assess recovery status and guide recovery actions but these quantities are poorly estimated in this rare species using traditional methods. Therefore, population size and spatial variation in density were estimated across the Arctic Coastal Plain (ACP) and Utqiagvik Triangle (Triangle) survey areas using spatio-temporal generalized additive models and compared to traditional design-based estimates. Compared to design-based estimates, model-based estimates were more precise and less variable between years. Moreover, data sets can be combined to produce common estimates, detection probability can be incorporated to estimate population size, and spatial density maps can be produced from model-based estimates. Across both data sets and when combined, Steller’s eider populations fluctuated with an approximate 6.53-year period (95% CI: 5.46, 7.93) with populations cycling from modeled posterior lows of 25–500 individuals and highs from 230 to > 2000 individuals across the ACP. Over the long term, the posterior 25-year geometric mean growth rate was −0.02 (95% CI: −0.07, 0.02), and shorter term growth rates were less well-estimated and fluctuated between positive and near zero. Density maps showed a high concentration in the northern part of the Triangle area and lower densities southward and across the ACP. Models fit to just the Triangle area indicated that eider density has been shifting northward though time, but this pattern was not supported in the sparse ACP data set, nor was it well-estimated when the ACP and Triangle data sets were combined. Given the strong cycle in this population, estimates of population size at similar cycle phases should be used for trend estimates.